Photoinduced Copolymerization of APMP-MMA: The Role of Reactive Hindered Amine APMP - Ting Zhang; Liuwa Fu; Zhikang Chen; Yanyan Cui; Xiaoxuan Liu (International Journal of Polymer Science)
4-Acryloyl-1,2,2,6,6-pentamethyl-piperidinol (APMP) is a reactive hindered amine that prolongs the service life of the polymeric materials and exhibits high stability, good resistance to extraction, and low toxicity. In this paper, a photoinduced free radical copolymerization of APMP and methyl methacrylate (MMA) is accomplished at ambient temperature in solution. APMP plays a key role in the copolymerization, owing to the nitroxides generated in situ from the moiety of 1,2,2,6,6-pentamethyl-piperidine under UV irradiation, and mediates the copolymerization, which is confirmed by the linear kinetics. With the increment of initial monomer feed ratios of APMP/MMA, both the copolymerization rate and the average molecular weight increase. According to the reactivity ratios from the extended Kelen-Tüdos (KT) method at high conversion by 1H NMR spectroscopy, a nonlinear model is established and the sequential distribution in the copolymers is also investigated. The dispersion of APMP units is regulated by the feed ratios and reactivity ratios.